The Prevalence of the Thrombotic SNPs rs6025, rs1799963, rs2066865, rs2289252 and rs8176719 in Patients with Venous Thromboembolism in the Czech Population - Tomas Kvasnicka MD, PhD; Renata Cifkova MD, PhD; Zuzana Zenahlikova MD, PhD; Petra Bobcikova MSc; Alena Syruckova MSc; Martin Sevcik MSc, PhD; Daniela Dusková MD, PhD; Jan Kvasnicka MD, PhD (Clinical and Applied Thrombosis/Hemostasis)
Introduction Study aimed to determine the occurrence of 5 thrombosis-related single-nucleotide polymorphisms (SNPs) in patients with venous thromboembolism (VTE) (n = 2630) and a control group (n = 2637) in the Czech population. Methods The following gene SNPs were detected in both groups: F5 Leiden (rs6025), F2 (rs1799963), FGG , fibrinogen gamma' (rs2066865), F11 (rs2289252) and ABO (rs8176719). Statistical analysis was performed using SAS statistical software with population genetics tools. Results Heterozygotes for F5 Leiden were associated with a 5.58-fold and homozygotes F5 Leiden with a 33.46-fold increased risk of VTE. At SNP rs1799963 ( F2 , prothrombin), only heterozygotes had a significant 3.9-fold increased risk of VTE. The findings at SNP rs2066865 (fibrinogen gamma', FGG ) showed a 1.37-fold increased risk of VTE for FGG heterozygotes and a 1.77-fold increased risk of VTE for FGG homozygotes. There is also a significant 1.42-fold increase risk of VTE in the heterozygotes and a 1.80-fold increase risk of VTE in the homozygotes of the SNP rs 2289252 ( F11 ). Further higher increases in the risk of VTE in both variants were found in patients with VTE at rs8176719 ( ABO , non-O). It corresponds to a 2.2-fold increase in the risk of VTE in heterozygotes and a 3.5-fold increase in the risk of VTE in homozygotes. Conclusion Besides F5 Leiden and prothrombin mutation, the study suggests that the gene polymorphisms of FGG (rs2066865), F11 (rs2289252) and ABO (rs8176719) play a role as an independent heritable risk factor for VTE in the Czech population.